ANALYSIS OF ADVERSE DRUG REACTION IN A TERTIARY CARE HOSPITAL: A RETROSPECTIVE STUDY - Roy, Dolly; Purkayastha, Ayan; Tigga, Rohit (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Adverse drug reaction (ADR) is an important cause of morbidity, mortality, and prolonged hospitalization. The objective of this study is to measure the incidence, types, and nature of ADR in a tertiary care hospital located in Silchar, Assam. Methods: A retrospective noninterventional analysis of all ADRs reported by ADR Monitoring Centre, Department of Pharmacology, Silchar Medical College, from March 2014 to February 2015 was performed. A total of 162 predesigned forms were used for collection of data. All forms were duly checked for completeness, if not, they were rejected. Results: A total of 162 forms were assessed of which 96 (59%) were females and 66 (41%) were males. The distribution of ADRs in different age groups were found to be 3 (1.85%) in 0-15 years, 71 (43.82%) in 16-30 years, 65 (40.12%) in 31-45 years, 8 (4.93%) in 46-60 years, and 15 (9.25%) in age group >60 years. 150 (92.6%) of the ADRs were serious and 12 (7.4%) were not serious. As per the World Health Organization causality assessment scale, 120 (74.07%) were probable and 42 (25.92%) were possible. The most common ADR was anaphylactic reaction (AR) in 69 (42.59%) patients. The drugs which commonly caused ADR were iron sucrose infusions, nevirapine, cephalosporins, antiprotozoals, nonsteroidal anti-inflammatory drugs, and quinolones followed by others. Conclusion: The majority of ADRs were probable. The most common ADR was AR caused by iron sucrose infusion. Different drugs caused differentADRs. ADRs thereby increase morbidity and mortality in patients as well as socioeconomic burden. Keywords: Adverse drug reaction, Anaphylactic reaction, Iron sucrose infusion, Noninterventional, Retrospective analysis.